Analysis of the role of financial leverage, good corporate governance, and firm size on profit management - Bakar, Armi; Nurlela, Nurlela; Esra, Martha Ayerza; Brastoro, Brastoro; Sandra, Amelia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to determine the influence of Financial Leverage, Good Corporate Governance, and Firm Size on manufacturing companies listed on the Indonesia Stock Exchange for the 2020 period during the Covid-19 pandemic. This research technique uses purposive sampling, so 25 companies were obtained as research samples. The source of data in this study is secondary data obtained from the www.idx.com and www.invesia.com sites in the form of an annual report (annula report) of manufacturing companies in the consumer goods sector. The model used in the study was cross section regression using data calculation application software, namely Eviews 10.0. The results of this study state that financial leverage does not affect managers in practicing earnings management. This article states that the average company has a safe influence in the sense that the company can pay back the debt used to finance the company's assets, so managers need to be more motivated to practice earnings management. Good Corporate Governance (KPI) does not play a role in Profit Management (DA), meaning that during the COVID-19 pandemic, the Good Corporate Governance implemented did not make managers practice profit management. Company Size (Ln Assets) has a role in Earnings Management (DA); the more significant the company will tend to reduce earnings management practices because large companies are politically more concerned by government agencies than small companies.